"This Other Germany, the Dark One": Post-Wall Memory Politics Surrounding the Neo-Nazi Riots in Rostock and Hoyerswerda. Issue 4 (1st December 2019) - Adaire, Esther
Abstract : This paper examines antiforeigner violence in the former East German towns of Hoyerswerda (1991) and Rostock-Lichtenhagen (1992) as a case study for both the heightened presence of neo-Nazi/skinhead groups in Germany following 1989/in the Wende period, and the memory politics employed by German politicians in the Bundestag, as well as in media discourse, with regards to the problems entailed in uniting two Germanys which had experienced entirely difference processes of Vergangenheitsbewältigung. My analysis of the riots focuses mainly on the mnemonic discourses surrounding them, in particular the work that the image of "the East German skinhead" does within the broader context of German memory politics. This paper is also situated within the context of present-day German politics with regards to shifting cultures of memory and the electoral success of Alternative for Germany.